Homozygous Familial Hypercholesterolemia: Case Series and Review of the Literature - Carlos H. Palacio; Theresa R. Harring; N. Thao T. Nguyen; John A. Goss; Christine A. O'Mahony (Case Reports in Transplantation)
Introduction. Familial hypercholesterolemia (FH) is caused by nonfunctioning low-density lipoprotein (LDL) receptors, resulting in high serum cholesterol. Two types of FH are described: the heterozygous form is diagnosed in adults and responds well to medical therapy; the homozygous form is rare, diagnosed in children, and often requires multiple treatments to prevent complications. Cholesterol accumulation in tissues produces common clinical manifestations including cutaneous xanthomas, coronary artery disease, and aortic stenosis. Treatment options consist of lifestyle modifications, lipid-lowering medications, LDL aphaeresis, and orthotopic liver transplantation (OLT). Case Presentation. Two patients with FH presented at young ages due to characteristic cutaneous xanthomas. The patients underwent cardiac testing that revealed atherosclerotic changes. The patients received maximal medical therapy, but only experienced a small decrease in serum cholesterol and LDL levels. After several years of medical treatment without improvement of symptoms, the patients were listed for OLT. The transplantations were successful, and only one patient had a postoperative complication of acute rejection, treated successfully. Currently, both patients are doing well with regression of the cutaneous xanthomas and atherosclerotic changes. Conclusion. OLT is a safe and effective option for patients with homozygous FH refractory to maximal medical therapy and may represent the optimal treatment for these patients.